Studi Fenomenologi Pengalaman Ibu dengan HIV/AIDS dalam Mengasuh Anak - Dewi Rahmawati; Eka Ernawati (Faletehan Health Journal, 2021)
The problems caused by HIV/AIDS may impact on the life of mothers with HIV/AIDS and affect the life of raising child. The complexity of HIV/AIDS effects helps mothers change their parenting styles in caring for themselves, their child and their family. The purpose of this study was to determine the experiences of mothers with HIV/AIDS in child care. The research design was qualitative with phenomenological approach. The results obtained three theme: psychological changes of mothers with HIV status, expectations for loved ones, the choice of dominant parenting style by PLWHA to their child. The impact of HIV disease still caused a psychological response to mothers in accepting their sick condition, impacting on the choice of dominant parenting styles between authoritarian and permissive. The complexity of the problems caused by HIV/AIDS required an integrated cross-sectoral health service system among department of religion, education and social affairs. It was important to Improve counseling services at hospitals and religion department to develop pre-marital counseling programs or topics for couples who will get married. It was also important to prepare or enrich themes of premarital guidance, especially the risks of HIV family or other communicable diseases. Education department should promote HIV approaches and preventions to students. Social department should ensure the availability of facilities for social health services that can accommodate children with HIV or children affected by HIV.